The incidence and infection status of the white mistletoe in Kazdağı fir forests of the West Black Sea region: A case study in Kökez Forest State Enterprise - İsmail Baysal (Turkish Journal of Forestry, 2023)
Mistletoes is an important biotic pest that needs to be studied in terms of its wide distribution in forest areas, its potential damage and predictability of adverse effects of climate change. In this study, the incidence and infection status of white mistletoe (Viscum album ssp. abietis (Wiesb.) Abromeit.) in fir trees were investigated. The study was conducted in pure Kazdağı fir (Abies nordmanniana subsp. equi-trojani (Asch. & Sint. ex Boiss.) Coode & Cullen) forests spread within the borders of Bolu Forest Regional Directorate, Aladağlar Forest District Directorate, Kökez Forest State Enterprise. In the study, firstly, the incidence of mistletoe in fir trees was determined in 159 circular experimental plots determined with systematically. The incidence and infection status of mistletoe in tree crown structure were also observed and evaluated for mistletoe detected trees. “The Six-Class Dwarf Mistletoe Rating System” was taken into account in determining the incidence and infection status of white mistletoe and the degree of mistletoe infection. According to the study results, it was determined that mistletoe was found at the highest rates in forest areas below 1100 m altitude on the basis of sampling plots and tree level. Also, it was found that the incidence of mistletoe increased with the aid of the increase by diameter classes. The average mistletoe incidence rate for total of 4696 measured fir trees was found to be 22.64%. Also, the average mistletoe infection rate was found to be 2,42 as moderate level for 1063 infected fir trees. Mistletoe infection in three different crown parts of the tree was the lowest for the lower crown part and the highest for the upper crown part. The incidence of mistletoe in tree crowns showed significant differences in terms of diameter classes (𝜒2 = 1171.631, df = 3, p = 0.000). It was determined that the degree of mistletoe infection increased with increasing diameter values, and it was highest for trees located at low elevations and southern aspects. The decrease in the presence of mistletoe on trees due to the increase with altitude (𝜒2 = 83.570, sd=2, p= 0.000) was similarly found to be a negative relationship between the mean mistletoe infection degree and altitude (r = -0.416; p<0.01). The mean mistletoe infection degree was found to be 0.58 for the sampling points.